PEPTIDES EXTRACTED FROM ARTEMISIA HERBA ALBA HAVE ANTIMICROBIAL ACTIVITY AGAINST FOODBORNE PATHOGENIC GRAM-POSITIVE BACTERIA - Fedhila, Sinda; Ben Lazhar, Wafa; Jeridi, Taoufik; Sanchis, Vincent; Gohar, Michel; Lereclus, Didier; Ben Hamida, Jeannette (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Artemisia herba alba, classified into the family of Asteraceae, is an aromatic herb that is traditionally used as a purgative and anti-pyretic folk medicine by rural people of south Tunisia. This study reports the first identification of antimicrobial peptides from this medicinal plant that inhibited the growth of several food-borne pathogenic bacteria. Materials and methods: The extraction and purification of peptidic agents from Artemisia herba alba, have been performed using precipitation by ammonium sulfate of a phosphate buffer crude extract obtained from the plant leaves, followed by reverse-phase HPLC on a C18 column. The mass of the peptides was estimated by SDS-PAGE electrophoresis, followed by a gel overlay assay and ultra-filtration through a 5 kDa cut-off membrane. Fractions from every purification steps were sampled and assayed for activity towards different food-borne bacterial strains pathogenic and non pathogenic to humans. Results: The phosphate buffer crude extract, as well as its ammonium sulfate precipitate, designated AS-P, inhibited the growth of Listeria monocytogenes, Staphylococcus aureus, Bacillus cereus sensu stricto and the new approved species Bacillus cytotoxicus. AS-P MICs (minimum inhibitory concentrations) ranged from 0.241 to 3.8 mg/ml proteins for L. monocytogenes and B. cereus sensu stricto (strains ATCC10987 and IP5832), respectively. The bioactive AS-P molecules were stable up to 10 minutes heating at 120°C and they resisted organic solvent effects. Antimicrobial activity of A. herba alba AS-P decreased to 40 and 60% after proteolytic treatment with trypsin and proteinase K, respectively, suggesting peptides being responsible for the A. herba alba AS-P activity. The mass of antibacterial A. herba alba peptides was estimated below 5 kDa. Two AS-P fractions, eluted at 40 and 37% acetonitrile, showed antibacterial activity when assayed against L. monocytogenes. Conclusion: A. herba alba could make a new source of novel natural anti-infective agents that could be used in food bio-preservation as natural additives or in human infectious disease treatments against multi-drug resistant pathogens.